2000
DOI: 10.1190/1.1444763
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and reconstruction of coherent energy with application to deep seismic reflection data

Abstract: Article: Van der Baan, M. and Paul, A. (2000) Recognition and reconstruction of coherent energy with application to deep seismic reflection data. Geophysics, 65 (2 Recognition and reconstruction of coherent energy with application to deep seismic reflection dataMirko van der Baan * and Anne Paul ‡ ABSTRACTReflections in deep seismic reflection data tend to be visible on only a limited number of traces in a common midpoint gather. To prevent stack degeneration, any noncoherent reflection energy has to be remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Both f ‐ k and τ ‐ p filters are often useful to suppress correlated noise such as ground roll or water column reverberations in large data volumes. Time‐ and space‐variant f ‐ k [ Duncan and Beresford , 1994] and τ ‐ p filters [e.g., van der Baan and Paul , 2000] are more sensitive to signal variations and can be employed in a data‐adaptive manner.…”
Section: Introductionmentioning
confidence: 99%
“…Both f ‐ k and τ ‐ p filters are often useful to suppress correlated noise such as ground roll or water column reverberations in large data volumes. Time‐ and space‐variant f ‐ k [ Duncan and Beresford , 1994] and τ ‐ p filters [e.g., van der Baan and Paul , 2000] are more sensitive to signal variations and can be employed in a data‐adaptive manner.…”
Section: Introductionmentioning
confidence: 99%
“…Va n der Baan and Paul (2000) have shown that the application of Gaussian statistics on local amplitude spectra after the application of a PCA allows for an efficient estimate of the presence of reflections and therefore their extraction. They used a very simple procedure to extract the desired reflections.…”
Section: An Examplementioning
confidence: 99%
“…However, these techniques do not consider that most of the energy of seismic signals is usually concentrated in a narrow slowness range. In this specific case, when the main signals are clearly separated, the inverse operation can be approximated by a sum of a small set of slowness components (Stoffa et al, 1981;Wenzel et al, 1982;van der Baan and Paul, 2000), or even by a single one (see, e.g., Gallart, 2003, 2004). Although full inverses are more accurate, a "lazy" inverse based on a single slowness component makes the inverse operation trivial, and it suffices for the applications of removing high-energy interfering waves and estimating low-energy waves, on which we focus.…”
Section: Filtering and Synthesismentioning
confidence: 99%
“…Widespread LSST applications are local-adaptive filters, e.g., the spatial-averaging filters on degree-of-polarization measures Gallart, 2003, 2004), or the adaptive f-k filters of Duncan and Beresford (1994); and instantaneous slowness measures (Milkereit, 1987;van der Baan and Paul, 2000;Hu and Stoffa, 2009). Hence, the LSST is found in leading-edge algorithms, such as CRS, to estimate the first-order-approximation parameters or stereotomography (Billette and Lambaré, 1998;Billette et al, 2003;Lambaré, 2008) to measure local slope in the event picking.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation